CT acquisition protocols for lung cancer screening-current landscape and the urgent need for consistency - Konrad, Mathis; Nischwitz, Emily; van der Lugt, Aad; Zahlmann, Gudrun; Palm, Viktoria; Chorostowska-Wynimko, Joanna; Prosch, Helmut; Mulshine, James L.; Kauczor, Hans-Ulrich (Insights into imaging, 2025)
Standardizing CT acquisition protocols reduces radiation exposure in lung cancer screening. Cross-continent collaboration will enhance understanding of diverse clinical practices. Survey results will inform future advancements in radiology sustainability efforts.
Gesehen am 09.12.2025